The Influence of Sustainability Reportdisclosure on Financial Perfomance Energy Sector Companies Listed the Indonesia Stock Exchange (IDX) Period 2021-2024 - Sembiring, Riska; Duma Megaria Elisabeth; Farida Sagala; Wesly Andri Simanjuntak (Universitas Methodist Indonesia, 2026)
This study aims to investigate and analyze the extent to which sustainability report disclosure influences the financial performance of companies operating within the energy sector that are officially listed on the Indonesia Stock Exchange (IDX). The sampling technique employed in this research is purposive sampling, applied to a population comprising 91 energy sector companies. From this population, a total of 10 energy sector companies listed on the Indonesia Stock Exchange were selected as the final research sample, accessed through the official IDX website at www.idx.co.id. The research adopts a quantitative approach as its primary methodology, with multiple linear regression analysis serving as the main data analysis technique used to examine the relationships between the variables under investigation. The findings of this study reveal that, when examined partially, economic performance demonstrates a positive yet statistically insignificant effect on financial performance, while environmental performance is found to exert a positive and statistically significant influence on financial performance. In contrast, social performance is shown to produce a negative and statistically insignificant impact on financial performance. However, when all three variables are tested simultaneously, the collective disclosure of economic performance, environmental performance, and social performance is found to have a significant and meaningful effect on financial performance as a whole. Furthermore, the results of the coefficient of determination test indicate that the combined variables of Economic Performance, Environmental Performance, and Social Performance are collectively capable of explaining approximately 13.7% of the total variation observed in the Financial Performance variable. The remaining 86.3% of the variation in financial performance is attributed to other variables and factors that were not incorporated into the regression model of the present study, suggesting that a broader range of determinants beyond those examined here may also play a substantial role in shaping the financial outcomes of energy sector companies listed on the Indonesia Stock Exchange.